Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Sekolah Menengah Kejuruan Swasta “X” Pekanbaru - Arhipen Yapentra (Akuntansi & Ekonomika, 2018)
The research was conducted at Private Vocational High School (SMK) “X” Pekanbaru. The purpose of this study is to determine the impact of Principal Leadership on Teacher Performance at Private Vocational High School (SMK) “X” Pekanbaru. The research method is descriptive with quantitative approach, with the research population is teachers of Private Vocational High School (SMK) "X" Pekanbaru as many as 34 teachers. While the number of samples determined in this study is the entire population minus 1 principal so that a total of 33 teachers. Based on simple linear regression equation Y = 7,166 + 1,235X. hence seen constants equal to 7,166, so influace of principal leadership on teacher performance is positive proven b = 1,235 meaning that every increase of headmaster leadership one unit will increase teacher performance at Private Vocational High School (SMK) “X” Pekanbaru at 1,235. The Leadership variable with tcount 8,128 > t table 2,039 with significant level 0.000 less than 5%. Then Ho is rejected and Ha accepted, meaning the leadership variable of principal has a positive and significant effect on teacher performance in Private Vocational High School (SMK) “X” Pekanbaru. The value of R-square (coefficient of determination) is 0,681, this indicates that the principal's leadership contributes to the teacher performance in Private Vocational High School “X” Pekanbaru by 86.2%, while the rest (100% - 68,1%) = 31,9% influenced by other variable outside of variable in this research